Donor‐defined mesenchymal stem cell antimicrobial potency against nontuberculous mycobacterium. (4th May 2021) - Bonfield, Tracey L.; Sutton, Morgan T.; Fletcher, David R.; Folz, Michael A.; Ragavapuram, Vaishnavi; Somoza, Rodrigo A.; Caplan, Arnold I.
Abstract: Chronic nontuberculous mycobacterial infections with Mycobacterium avium and Mycobacterium intracellulare complicate bronchiectasis, chronic obstructive airway disease, and the health of aging individuals. These insidious intracellular pathogens cause considerable morbidity and eventual mortality in individuals colonized with these bacteria. Current treatment regimens with antibiotic macrolides are both toxic and often inefficient at providing infection resolution. In this article, we demonstrate that human marrow‐derived mesenchymal stem cells are antimicrobial and anti‐inflammatory in vitro and in the context of an in vivo sustained infection of either M. avium and/or M. intracellulare . Abstract : Mesenchymal stem cells (hMSCs) anti‐non‐tuberculous mycobacteria activity: hMSCs have impressive clinical and therapeutic benefits including antimicrobial and antibiotic enhancing potency. hMSCs are antimicrobial against Mycobacterium avium and Mycobacteria intracellulare, which complicate a variety of pulmonary diseases. hMSC effects are mediated through altering host immunity and direct production of soluble mediators. Potency is both pathogen and donor hMSC specific.